2021
DOI: 10.1111/1346-8138.16049
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of zinc deficiency in epidermal growth factor receptor inhibitor‐induced xerotic dermatitis

Abstract: Cancer treatment with epidermal growth factor receptor inhibitors (EGFRIs) often induces severe xerotic dermatitis. Various irritants facilitate development of dermatitis in xerotic skin. As zinc deficiency plays a role in the development of irritant dermatitis, we measured serum zinc levels in 25 patients with xerotic dermatitis due to treatment with EGFRIs. Of these patients, nine were treated with EGFR tyrosine kinase inhibitors and 16 were treated with anti‐EGFR antibody alone or in combination with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Hence, downregulation of TRPM7 induced by TKI might affect intracellular concentration of Zn 2+ . Clinical investigations showed reduced serum Zn 2+ as adverse effect of EGFR inhibition and Zn 2+ supplementation was able to reduce dermatitis these patients (185). Of importance, Zn 2+ is a potent antioxidant and its deficiency is associated with mitochondrial and endoplasmic reticulum (ER) stresses, increased ROS production and dysregulation of cellular metabolism (186).…”
Section: Cardiac Arrhythmia and Ischemic Heart Diseasementioning
confidence: 99%
“…Hence, downregulation of TRPM7 induced by TKI might affect intracellular concentration of Zn 2+ . Clinical investigations showed reduced serum Zn 2+ as adverse effect of EGFR inhibition and Zn 2+ supplementation was able to reduce dermatitis these patients (185). Of importance, Zn 2+ is a potent antioxidant and its deficiency is associated with mitochondrial and endoplasmic reticulum (ER) stresses, increased ROS production and dysregulation of cellular metabolism (186).…”
Section: Cardiac Arrhythmia and Ischemic Heart Diseasementioning
confidence: 99%
“…The skin is known to be one of the systems that is most susceptible to zinc de ciency, hence the rash and itching [1]. We also reported that a zinc homeostasis disorder might cause the development of skin xerosis in patients with colorectal cancer treated with FPOX plus anti-EGFR antibody [22]. The skin conditions and zinc levels appeared to be closely correlated.…”
Section: Discussionmentioning
confidence: 72%
“…A case of necrolytic migratory erythema (NME)‐like skin eruptions has been reported in a patient after erlotinib use and has been found to improve with zinc supplementation for a month 17 . A study on patients with EGFR‐TKI‐induced xerotic dermatitis due to zinc deficiency has shown that zinc supplementation can ameliorate their symptoms 18 …”
Section: Introductionmentioning
confidence: 99%